Comparison Between Platelet-Rich Plasma Single- and Double-Spin Centrifugation to Treat Androgenetic Alopecia: A Systematic Review - Stella Skolastika Suwana; Komang Ardi Wahyuningsih; Laurentius Aswin Pramono (Syntax Corporation, 2022)
There are no established guidelines for the management of androgenetic alopecia (AGA). A new therapy with promising results is Platelet-Rich Plasma (PRP). PRP has a variety of preparation methods, such as single spin and double spin centrifugation and still there is no consensus on the method of preparation. There is controversy of which preparation method is better. We searched PubMed, EBSCO, Clinical Key, ProQuest, Cochrane Library, Science Direct, Clinical Trial, Open Access, Wolters Kluwer, Google Scholar, GARUDA, and AtmaLib until Oct 2020 for human studies using PRP for AGA treatment. We assessed 3375 papers; 6 studies met the inclusion criteria and evaluated 128 AGA patients, 112 male and 16 female, 18-63 years old. Participants varied from type II-VI based on the Hamilton-Norwood classification system and degree 2 based on the Ludwig classification system. Four studies used the single-spin centrifugation PRP preparation method and two studies used the double-spin PRP preparation method. The studies stated the increases in growth factor levels. All studies showed PRP significantly affected hair growth in AGA patients. PRP has been shown to increase hair growth parameters in form of hair density (P <0.0001). PRP has been shown to increase hair density and hair count. Growth factors in PRP induce cell proliferation and tissue angiogenesis. The results of single-spin centrifugation preparation method provide a greater increase in hair density. But, data reports from the study did not allow comparisons to determine the best PRP preparation method for AGA treatment. Therefore further study is needed.